2011
DOI: 10.1111/j.1468-3083.2010.03795.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence and risk factors of thromboembolism in stage IV melanoma

Abstract: We found as high a prevalence of VTE in stage IV melanoma as in lung and gastrointestinal cancers. All patients suffered thrombotic events when they were treated with chemotherapy and at home when they stopped heparin prophylaxis. Therefore, heparin prophylaxis should be maintained at home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…In addition, a promising in vitro data for the PAR-1 antagonist, SCH79797, has been recently reported (34). Furthermore, a correlation between thrombosis and cancer patients has been reported in several cancers including melanoma, and it was demonstrated that anti-coagulant therapy prolonged the survival term in cancer patients (7, 35). Nevertheless, platelet activation can be induced by another PAR, at high thrombin concentrations (5).…”
Section: Par-1 As a Therapeutic Target In Melanoma Patientsmentioning
confidence: 95%
“…In addition, a promising in vitro data for the PAR-1 antagonist, SCH79797, has been recently reported (34). Furthermore, a correlation between thrombosis and cancer patients has been reported in several cancers including melanoma, and it was demonstrated that anti-coagulant therapy prolonged the survival term in cancer patients (7, 35). Nevertheless, platelet activation can be induced by another PAR, at high thrombin concentrations (5).…”
Section: Par-1 As a Therapeutic Target In Melanoma Patientsmentioning
confidence: 95%
“…Among the different cancer types, the VTE incidence is especially high in malignant melanoma, occurring in approximately 25% of melanoma patients [3]. An association between an enhanced risk of thrombotic complications and an increase of von Willebrand factor (VWF) levels in plasma and tumor tissue of patients with distinct malignancies has been described by multiple clinical studies for specific malignancies [47].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Especially in malignant melanoma patients, the incidence of venous thromboembolism (VTE) is ;25%. 18 Moreover, clinical studies demonstrate that treatment with anticoagulant low-molecular-weight heparins (LMWHs) improves the outcome of distinct cancer patients. 19 Based on these observations, we postulate that EC activation, followed by the generation of VWF fibers in tumor vasculature, promotes cancer-associated hypercoagulopathy and facilitates metastasis.…”
mentioning
confidence: 99%